2017
DOI: 10.15448/1980-6523.2017.2.28930
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial action of red and green propolis extract in infected root canal

Abstract: OBJECTIVE: This study investigated the antibacterial action of 30% red propolis, 40% green propolis and 2.5% sodium hypochlorite with irrigation protocols in infected root canals. METHODS: During 60 days, twenty-four root canals were inoculated with E. faecalis. In all experimental groups were performed root canal preparation and two irrigation protocols -passive ultrasonic irrigation and conventional irrigation. In the groups 1, 3, 5 and 7 it were made root canal preparation associated to conventional irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…However, a study verified that Brazilian green propolis was only susceptible to E. faecalis 28 and another recent study showed that green propolis was effective on E. faecalis as irrigant solution, but not able to inhibit bacteria. 29 10% propolis ratio may not form an inhibitory zone so, the present study is in accordance with those researches. Low propolis level in the drop used in the study could be the reason for inferior results on E. faecalis.…”
Section: Acknowledgementsupporting
confidence: 92%
“…However, a study verified that Brazilian green propolis was only susceptible to E. faecalis 28 and another recent study showed that green propolis was effective on E. faecalis as irrigant solution, but not able to inhibit bacteria. 29 10% propolis ratio may not form an inhibitory zone so, the present study is in accordance with those researches. Low propolis level in the drop used in the study could be the reason for inferior results on E. faecalis.…”
Section: Acknowledgementsupporting
confidence: 92%
“…A clinical study reports a positive efficacy of propolis-containing mouthwash in reducing plaque index and gingival index. 24 The phenolic components are responsible for the antimicrobial activity of propolis. Studies show that propolis has more than 300 components.…”
Section: Antimicrobial Effect Of the Productsmentioning
confidence: 99%